Korporasi Sebagai Subyek Hukum dalam Tindak Pidana Lingkungan Hidup - Pratama, T. Andana Harris; Ali, Muhammad; Fadil, Fadil (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
This paper aims to see how corporate responsibility in committing environmental crimes as one of the legal subjects. In order to approach this problem, theoretical references are used from their books by Philipus M. Hadjon and Tatiek Sri Djatmiati who argue that in the civil law system, the first approach is the law approach. The data were collected through the applicable laws and regulations in Indonesia and were analyzed qualitatively. This paper concludes that legal responsibility in criminal acts of environmental damage is not only borne by individuals, but also legal entities or corporations as subjects of criminal law. In this case the board and the corporation have the same burden of responsibility in committing an environmental crime.